A new approach to textual criticism an introduction to the coherence-based genealogical method - Wasserman, Tommy 1970-; Gurry, Peter J. (Atlanta Society of Biblical Literature, 2017)
"Cover" -- "Contents" -- "Acknowledgments" -- "Figures and Tables" -- "Abbreviations" -- "Introduction" -- "Overview of the Method" -- "Pregenealogical Coherence" -- "Genealogical Coherence" -- "The Global Stemma" -- "Limitations and Future Improvements" -- "Further Reading" -- "Glossary
Keywords: Bibel; Textkritik; Einleitung; Bible ; Criticism, Textual; Electronic books